PENGATURAN PHK EFISIENSI DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DAN UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Masrifatun Mahmudah; Markus, Dwi Pratiwi (JUSTISI, 2022)
The purpose of this study is to describe the arrangement of layoffs for reasons of efficiency in the Manpower Act and the Job Creation Act, and to analyze the legal position of efficiency layoffs in the Job Creation Law against the Constitutional Court Decision No. 19/PUU-IX/2011. This normative research was conducted by means of a literature study using primary and secondary legal materials. The result of this study is that Article 154A paragraph (1) letter b of the Job Creation Law regulates layoffs on the grounds of efficiency that they may be carried out even without being followed by the permanent closure of the company. However, Article 154A paragraph (1) letter b has violated the Constitutional Court Decision No. 19/PUU-IX/2011 which states that efficiency layoffs must be followed by permanent closure of the company. Therefore, Article 154A paragraph (1) letter b contradicts the Constitutional Court Decision which has a higher position than the law because the source of the validity of the Constitutional Court's decision is the 1945 Constitution.